2016
DOI: 10.17507/tpls.0612.11
|View full text |Cite
|
Sign up to set email alerts
|

Procedural Rhetoric: An Alternative to Traditional Academic Writing Programs

Abstract: Abstract-A host of movements have been performed to broaden English language learners' writing scholarship. A major rethink of L2 writing materials is what syllabus designers should pursue in some collegiate contexts; all the more so because writing is considered as a scholarly skill for English language learners to do academic assignments and manifest their academic attainments in different academic areas. Having this in mind, the present study explored the implications of new English writing course syllabuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The different concepts of phrases and clauses -noun, adverbial, adjectival, prepositional and verb phrases as well as noun, adverbial, and adjectival clauses -have to be at the writer's finger tips as the knowledge to arrange words in sentences (by exploiting all these phrases and clauses) assists the writers to find their own writing style. Kiasi & Alavi (2016) in their research found that the experimental group -which are equipped with grammar and syntactic skills (passive, modals, adverbial, adjective phrase and so forth) performed better in writing in comparison to the control group which did not get such treatment. The skill of organizing phrases and clauses can give impact to the writinghelp in shaping the paragraph more systematically -that provides ease of reading to the readers.…”
Section: English Grammar Knowledge and Skills Facilitate Students Writingmentioning
confidence: 97%
See 1 more Smart Citation
“…The different concepts of phrases and clauses -noun, adverbial, adjectival, prepositional and verb phrases as well as noun, adverbial, and adjectival clauses -have to be at the writer's finger tips as the knowledge to arrange words in sentences (by exploiting all these phrases and clauses) assists the writers to find their own writing style. Kiasi & Alavi (2016) in their research found that the experimental group -which are equipped with grammar and syntactic skills (passive, modals, adverbial, adjective phrase and so forth) performed better in writing in comparison to the control group which did not get such treatment. The skill of organizing phrases and clauses can give impact to the writinghelp in shaping the paragraph more systematically -that provides ease of reading to the readers.…”
Section: English Grammar Knowledge and Skills Facilitate Students Writingmentioning
confidence: 97%
“…Wrong use of these verb components leads to misinterpretation of content. Lacking of verbs knowledge decreases one's ability to express their thoughts (Kiasi, & Alavi, 2016). With the twelve common tenses that all English users should know, L2 learners especially can benefit from it as tenses help writers to organize their content more efficiently with appropriate time frame planned.…”
Section: English Grammar Knowledge and Skills Facilitate Students Writingmentioning
confidence: 99%